Outcomes assessment: implications for nursing education. - Thompson, Cesarina; Bartels, Jean E (Journal of Professional Nursing, 1999)
In response to public criticisms about the outcomes of higher education, colleges and universities have implemented comprehensive assessment programs. In nursing education, outcomes assessment has become a criteria for accreditation. Yet, currently no guidelines exist describing “best practices” in nursing education outcomes assessment. Experts in educational assessment provide helpful guidelines for nurse educators as they establish comprehensive assessment plans. The authors provide a review of the literature in the field of assessment and offer strategies for developing successful assessment programs in nursing education.
Keywords: *Benchmarking/og [Organization & Administration]; *Education, Nursing/st [Standards]; *Guidelines as Topic; *Outcome Assessment, Health Care/og [Organization & Administration]; *Program Evaluation/mt [Methods]; Accreditation; Accreditation/og [Organization & Administration]; Benchmarking; Curriculum; Education, Nursing; Guidelines; Humans; Nursing education; Outcome Assessment (Health Care); Outcomes assessment; Program Evaluation; Program evaluation; accreditation; curriculum; dept.nur; health care quality; human; methodology; nursing education; organization and management; outcome assessment; practice guideline; quality control; review; standard